Inovasi Pemanfaatan Limbah Kertas dalam Pembuatan Panel Papercrete Ramah Lingkungan dengan Penambahan Ampas Tebu (Saccharum officinarum L.) sebagai Filler - Daffa Fathan Mubina; Mohammad Jidan Alhasani; Agus Widayoko (SMA Trensains Muhammadiyah Sragen, 2025)
In the process of fulfilling the needs of life, humans often use paper for various purposes. This causes the paper waste generated to be a challenge that must be managed properly. In 2023, the National Waste Management Information System (SIPSN) explained that the total waste of paper or cardboard in Indonesia reached 11,034 tons. The accumulation of waste has the potential to pollute and damage the ecosystem. One potential solution is to convert waste into valuable goods, one of which is papercrete panels. The cellulose content of paper waste and bagasse can be utilized in the manufacture of papercrete panels. This research aims to utilize paper waste and bagasse as papercrete panels while analyzing the effectiveness of the product. The research method uses a qualitative descriptive approach with data collection through observation, experimentation, and literature study. Tests included visible properties test, compressive strength test, water absorption test, and density test. The results showed that the product had a flat surface, no cracks or defects. In addition, the product also has a compressive strength of 2.7 MPa, water absorption of 23.63%, and density of 699.71 kg/m³. The test results have met SNI 03-0691-1996 and SNI 03-2847-2013. Based on the tests conducted, this research successfully identified the effectiveness of papercrete panels. This product offers an economical, lightweight, and environmentally friendly construction material.